Glycaemic control in type 2 diabetes patients and its predictors: a retrospective database study at a tertiary care diabetes centre in Ningbo, China - Li, Jialin; Chattopadhyay, Kaushik; Xu, Miao; Chen, Yanshu; Hu, Fangfang; Chu, Jianping; Li, Li (BMJ Publishing Group Ltd, 2018)
Objectives: The objectives of the study were to assess glycaemic control in patients with type 2 diabetes (T2DM) at a tertiary care diabetes centre in Ningbo, China and to determine factors that independently predict their glycaemic control.